Accessibility of shopping malls for persons with disabilities (PwDs) in compliance with Malaysian standards - Bashiti, Alaa (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2016)
This research discusses the issue of accessibility, connectivity and usability in the facilities used by persons with disabilities (PwDs) in Malaysian shopping malls and the significance of the latest Malaysian Standards (MS 1184:2014), the Universal Design and Accessibility in the Built Environment-Code of Practice in evaluating shopping malls. The study identifies whether the provided facilities accord with the latest Malaysian standards (MS 1184:2014). The sampled shopping malls comprised Ikea in Damansara, Suria Kuala Lumpur Convention Centre (KLCC) in Kuala Lumpur and Alamanda in Putrajaya. Data were collected using semi-structured interviews with the visually impaired, hearing impaired person, and wheelchair and crutches users to determine their perception on the level of accessibility of these buildings. Access audit and site observations were also carried out to assess the buildings' accessibility, connectivity, mobility and reachability. The results show that Suria KLCC scored 80.35% for compliance with the design requirements, followed by Ikea with 74.11%, and Alamanda with 70.58%. It is hoped that the research can benefit people from all walks of life as well as generate more ideas to improve the accessibility of shopping malls for the PwDs.